The role of lung ultrasound in the COVID-19 - D. O. Starostin; A. N. Kuzovlev (Вестник анестезиологии и реаниматологии)
Currently, a certain amount of clinical data has been accumulated about the basics of lung ultrasound examination in the patients with pneumonia caused by COVID-19.The use of ultrasound can be informative for assessing the state at the pre-hospital stage and triage, identifying patients with minor forms of the disease and their consequent routing. This review of literature has focused on the principles of the diagnosis of pneumonia using ultrasound in the context of the COVID-19 pandemic.